2021
DOI: 10.1089/neu.2018.6080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antiplatelet and Anticoagulant Drug Use on Outcomes after Chronic Subdural Hematoma Drainage

Abstract: We aim to describe the outcomes after chronic subdural hematoma drainage (CSDH) management in a large cohort of patients on antithrombotic drugs, either antiplatelets or anticoagulants, at presentation and to inform clinical decision making on the timing of surgery and recommencement of these drugs. We used data from a previous UK-based multi-center, prospective cohort study. Outcomes included recurrence within 60 days, functional outcome at discharge, and thromboembolic event during hospital stay. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
(39 reference statements)
0
27
0
4
Order By: Relevance
“…There were no cases of early recurrence (<1 week); Kamenova et al and Poon et al reported 28 cases of late recurrence and 13 thromboembolic events after surgery, without any statistically significant difference between patients who underwent discontinuation or not ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…There were no cases of early recurrence (<1 week); Kamenova et al and Poon et al reported 28 cases of late recurrence and 13 thromboembolic events after surgery, without any statistically significant difference between patients who underwent discontinuation or not ( 6 , 8 ).…”
Section: Discussionmentioning
confidence: 93%
“…Four hundred thirty-nine patients were collected in this group. Four hundred seven (92.7%) patients discontinued LDAA on admission while 32 patients (7.3%) at least 5 days before surgery due to minor symptom presentation ( 6 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations